Die Waldverhältnisse im Peloponnes unter besonderer Berücksichtigung der Entwaldung und Aufforstung - Beuermann, Arnold (ERDKUNDE, 1956)
The topic of this paper is dealt with in three sections: 1. The ecological conditions of the important woodland- forming tree species are described according to their areas (cf. map) and vertical (cf. fig. 1) distribution; these species are: Pinus halepensis, Pinus Pallasiana, Abies cephalonica, the Arbutus varieties, Castanea and the maquis. lt emerges clearly that the widest distribution of maquis with Q. coccifera and arbutus is found in the eastern and southeastern areas of low rainfall. The main areas of coniferous forests with Pinus Pallasiana and Abies cephalonica are limited to the !arge mountainous regions, viz. Taygetos, Parnon, Maenalon, Olonos, Chelmos and Ziria. The formerly large cypress forests have disappeared almost completely, some of those still extant are private property. The quercus varieties are dominant in the southwestern Peloponnese, Pinus halepensis prevails in the western Nomos Elias, the area Pyrgos-Olympia. For the first time detailed data of the size in hectares of these wooded areas is given (cf. table) on the basis of Greek forestry literature as well as information provided by Greek forestry offices. Not only are the tree species within these major regions given, but it is also stated for each of the forest districts (a) whether they are owned by the state, a civil parish, a eo-operative, the church or by private individuals, and (b) whether they are high, middle or low forests. 2. Deforestation is dealt with in outline in this section and the responsible historical as well as climatic factors are pointed out. Amongst the historical causes attention is given to destructive war raids, shipbuilding and railway construction and also to the consequences of transhumance and pastoralism, viz. damage clone to trees by the animals feeding upon them, and overgrazing. Examples of soil erosion as a result of deforestation are given for the northwest of the Maenalon Mountains where in 1912, in a small tributary valley, shepherds burnt down a tract of forest in the interest of pasture. 3. Reafforestation: potentialities, results and problems of reafforestation are discussed and the technical, financial and sociological difficulties that have to be overcome are pointed out.